Utopia or dystopia – deterrents to ecotourism development in Fiji. Issue 2 (3rd April 2023) - Prentice, Catherine; Kundra, Sakul; Alam, Mumtaz; Alam, Mohammad Afsar; Nguyen, Mai
Abstract: This paper draws on sustainability and ecotourism literature and aims to identify the deterrents to ecotourism development. The research opted to use Abaca Ecotourism Park, located in the Koroyanitu National Heritage Park in Western Viti Levu Fiji, as a case study. Three studies exploring management, local residents, and tourists' perspectives were undertaken to determine the factors that deter from the further development of the selected ecotourism project. Study 1 conducted an interview with the management team of the ecotourism park to gain insights into the factors that influenced the project's development. Study 2 was undertaken with the villagers who reside in the region where the ecotourism park is located. Longitudinal secondary research covering 20 years of data was used in Study 3 to identify tourists' visitation and consumption patterns. Some findings were consistent across the three studies. The results reveal a range of deterrents to the ecotourism development, including infrastructure constraints, issues related to inequality, overdependence on neighbouring countries, and political vulnerabilities. The implications for the literature and practitioners conclude the paper.